The thing about Pam : the complete limited series [videorecording (DVD)] - Zellweger, Renée, 1969-; Duhamel, Josh, 1972-; Greer, Judy, 1975-; Adlon, Gideon, 1997-; Bridgers, Sean; Spoke, Suanne; Brandt, Mac, 1980-; Mixon, Katy, 1981-; Fleshler, Glenn (Universal, 2022)
Based on the 2011 murder of Betsy Faria that resulted in her husband, Russ' conviction. When his conviction was overturned, the crime set off a chain of events that exposed a diabolical scheme deeply involving Pam Hupp.